TWEAK-Fn14 signaling protects mice from pulmonary fibrosis by inhibiting fibroblast activation and recruiting pro-regenerative macrophages - Li Liu; Pei Wu; Yuqi Wei; Meng Lu; Haiyan Ge; Ping Wang; Jianlong Sun; Tiffany Horng; Xiucheng Liu; Xiaoyong Shen; Lingyun Sun; Ying Xi (Cell Reports)
Summary: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease characterized by excess accumulation of the extracellular matrix (ECM). The role of macrophage-fibroblast crosstalk in lung fibrogenesis is incompletely understood. Here we found that fibroblast growth factor-inducible molecule 14 (Fn14), the receptor for tumor necrosis factor-like weak inducer of apoptosis (TWEAK) is highly induced in myofibroblasts in the lungs of IPF patients and the bleomycin-induced lung fibrosis model. TWEAK-Fn14 signaling inhibits fibroblast activation and ECM synthesis and induces chemokine expression to recruit monocytes/macrophages into the lung. Fn14 deficiency increases ECM production and impairs macrophage infiltration and differentiation, leading to exacerbated lung fibrosis and impaired alveolar regeneration in a bleomycin model. Interestingly, Fn14 deficiency diminishes an injury-induced SiglecF− CD11b− MHCIIlo intermediate macrophage (IntermM) subpopulation, which promotes alveolar type II (AT2) cell proliferation in organoid cultures. These results collectively demonstrate a protective role of TWEAK-Fn14 signaling in lung fibrosis, highlighting the complexities and multilayered regulation of macrophage-fibroblast crosstalk.